British Cycling Federation training guidelines - Keen, P.
As a result of several years of cycling specific research, conducted by Peter Keen, BCF Consultant Exercise Physiologist, based at Bishop Otter College, Chichester, the following training guidelines have been prepared with assistance from Tony Yorke, BCF Coaching Development Officer. This research programme is continuing and is funded through a National Coaching Foundation Sports Science Education Grant, provided by the Sports Council and administered by the British Cycling Federation (BCF). Four Levels of Training Intensity Each of the four levels of training intensity identified by Peter Keen is controlled by working at a specified heart rate, in beats per minute (BPM), relative to your maximum heart rate (MHR). Alternatively, the guide provides a description of how each of the four levels should 'feel' when being performed correctly, and these sensations should remain constant at each level of training, irrespective of the degree of fitness achieved. Note that if, whilst training at a particular level, the effort made is either too hard or too easy against the indicated heart rate range for that level, then the training effect will shift to either the level above, or the level below, the one intended. This is a particular problem when training in a group situation. Training at levels 1 and 2 can be performed in a group where additional skills may be simultaneously acquired, but there is a real danger of losing control of the purpose of your training session. Avoid being compelled by other members of the group to train at a level which is not right for you for that session.